“Rise up and walk”: Tracing the trajectory of the Carnegie discourse and plotting a way forward - Bowers-Du Toit, Nadine (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This article will provide a comparative analysis of the findings of the first Carnegie Commission on the Poor White Problem, 1932, and the second Carnegie second Carnegie Inquiry into Poverty and Development in Southern Africa, 1982, with regards to the role of the church as an agent of change. It also seeks to navigate the tension inherent in the “double legacy” of the church’s historical engagement with issues of poverty and inequality in order to reflect on its current praxis. The article, therefore, highlights both the challenges and opportunities for the church’s role as we celebrate 20 years of democracy.